2007
DOI: 10.1016/j.jaad.2006.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid antibodies in patients with autoimmune blistering disease

Abstract: Objective: To determine the serum levels and frequency of antiphospholipid antibodies (aPLs) and confirm the clinical importance of this antibodies in patients with autoimmune blistering disease (ABD). Methods:IgG and IgM anti-cardiolipin antibodies (aCL), IgG anti-cardiolipin-β 2 glycoprotein I complex antibody (aCL/β 2 GPI), and IgG anti-phosphatidylserine-prothrombin complex antibody (aPS/PT) were examined with an enzyme-linked immunosorbent assay in 71 patients with ABD, including pemphigus vulgaris, pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 19 publications
0
21
2
Order By: Relevance
“…We demonstrated the presence of two non-classic antiphospholipid antibodies, aPS-β2GPI and aPT-PT, among ABD patients. Nevertheless, in contrast to Echigo et al [6], classic aPL such as aCL and B2GPI were not found to be more prevalent in our cohort in comparison to control sera. This may be attributed in part to the immunosuppressive therapy of our patients.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We demonstrated the presence of two non-classic antiphospholipid antibodies, aPS-β2GPI and aPT-PT, among ABD patients. Nevertheless, in contrast to Echigo et al [6], classic aPL such as aCL and B2GPI were not found to be more prevalent in our cohort in comparison to control sera. This may be attributed in part to the immunosuppressive therapy of our patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Echigo et al [6] studied the sera of 71 patients with pemphigus vulgaris, pemphigus foliaceus, and bullous pemphigoid for anticardiolipin antibodies (aCL), anticardiolipin-b2 glycoprotein I complex antibody and antiphosphatidylserine -prothrombin complex using an enzyme-linked immunosorbent assay. They found that the prevalence of IgG and IgM aCL, aCL-β2GPI, and IgG aPS-PT was positive for 22.4%, 9.1%, 9.9%, and 25.4% of the ABD patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The type of organs involved varied and included the brain and lung. 19 A recent population-based study found that patients with BP are 3 times as likely to develop pulmonary embolism. 20 To the best of our knowledge, this is the first populationbased study to investigate the risk of stroke in a national cohort of patients with BP.…”
Section: Discussionmentioning
confidence: 99%
“…Among 10 patients who tested positive for aPLs, 7 patients had thromboembolisms, although most of them were clinically asymptomatic. 19 aPLs can produce a prothrombic state through inhibition of natural anticoagulant pathways, inhibition of fibrinolytic mechanisms, and induction of endothelial cell procoagulant activity. These processes predispose the patient to thrombotic events, particularly ischemic stroke.…”
Section: Yang Et Al Increased Risk Of Stroke In Patients With Bpmentioning
confidence: 99%
“…For instance, one recent study reported that thromboembolism occurred in patients with autoimmune blistering disease [19]. This process may correlate BP to thrombotic events.…”
Section: Discussionmentioning
confidence: 99%